Understanding Effective Delivery of Patient and Family Education in Pediatric Oncology: A Systematic Review From the Children's Oncology Group. (November 2016) - Rodgers, Cheryl C.; Laing, Catherine M.; Herring, Ruth Anne; Tena, Nancy; Leonardelli, Adrianne; Hockenberry, Marilyn; Hendricks-Ferguson, Verna
A diagnosis of childhood cancer is a life-changing event for the entire family. Parents must not only deal with the cancer diagnosis but also acquire new knowledge and skills to care safely for their child at home. Best practices for delivery of patient/family education after a new diagnosis of childhood cancer are currently unknown. The purpose of this systematic review was to evaluate the existing body of evidence to determine the current state of knowledge regarding the delivery of education to newly diagnosed pediatric oncology patients and families. Eighty-three articles regarding educational methods, content, influencing factors, and interventions for newly diagnosed pediatric patients with cancer or other chronic illnesses were systematically identified, summarized, and appraised according to the Grading of Recommendations Assessment, Development, and Evaluation criteria. Based on the evidence, 10 recommendations for practice were identified. These recommendations address delivery methods, content, influencing factors, and educational interventions for parents and siblings. Transferring these recommendations into practice may enhance the quality of education delivered by health care providers and received by patients and families following a new diagnosis of childhood cancer.